Alkaline polyol fractionation of sugarcane bagasse and eucalyptus grandis into feedstock for value added chemicals and materials - Pius, Moses Tuutaleni (Stellenbosch : Stellenbosch University, 2017)
Thesis (MEng)--Stellenbosch University, 2017.